Pengaruh Human Relation Dan Gaya Kepemimpinan Transfromasional Terhadap Etos Kerja Karyawan Pada PT. Nusa Guna Prima Jaya Kecamatan Ungar Kabupaten Karimun - Nur Marlina; Seno Andri (Departement of Mathematics Education, 2023)
This research was conducted with the aim to determine the effect of human relations and transformational leadership style on the work ethic of employees at PT. Nusa Guna Prima Jaya, Ungar District, Karimun Regency. Human relations and transformational leadership style as independent variables (X1, X2) while employee work ethic as the dependent variable (Y). The problem that occurs in this study is the decrease in employee performance so that it has an impact on the employee's work ethic itself and the occurrence of fluctuating employee turnover and employee absenteeism which increases every year. This can be seen from the data on labor turnover and company attendance. The sample for this research was taken as many as 67 respondents from the population calculated using the slovin formula. The data obtained from the results of the questionnaire and then processed to then be tested with statistics through the SPSS program. The data analysis technique used is validity and reliability test, multiple linear analysis, coefficient of determination, t test and F test. Based on the results of the tests performed it shows that human relations and transformational leadership style have a positive and significant effect on the work ethic of employees at PT. Nusa Guna Prima Jaya, Ungar District, Karimun Regency.